Analisis Nilai Pendidikan Karakter pada Novel Cinta dalam Ikhlas Karya Abay Adhitya - Maulana, Nanang; Sumyati, Sumyati (Jurnal Artikula, 2021)
This research has a background, among others, weak and declining values ​​of character education in students. This study aims to describe: the value of character education. The method used in this research is descriptive method. The object of research is the novel Cinta dalam Ikhlas by Abay Adhitya. The object of research is the value of character education in the novel Cinta dalam Ikhlas by Abay Adhitya. The technique used in this research is library, reading and note-taking technique. The researcher recorded the data in the novel Cinta dalam Ikhlas by Abay Adhitya and books for writing reference. Data analysis technique the writer chose content analysis technique. The results of this study can be concluded that the value of character education includes (a) attitudes and behavior in relation to God, (b) attitudes and behavior in relation to oneself, (c) attitudes and behavior in relation to family, (d) attitudes and behavior in relation to society and the nation, (e) attitudes and behavior in relation to the natural surroundings.